ChemInform Abstract: Catalytic C—H Allylation and Benzylation of Pyrazoles. Issue 22 (15th May 2015) - Bae, Seri; Jang, Ha‐Lim; Jung, Haeun; Joo, Jung Min
Abstract: A new strategy for the preparation of C5‐allyl and benzyl pyrazoles is developed.